Media as Propaganda for Law Enforcement and Justice in the Philippines - Atanacio, Sharmaine; Amparo, Cristia Shiena S. (The Journal of Society and Media, 2024)
The poor justice system in the Philippines intensifies poverty among underprivileged people. It leaves them with no choice but to handle conflicts through Trial by Publicity or go to radio or TV stations and programs for their brawls to broadcast. The belief that immediate justice will be served made these Filipinos continuously choose these avenues to resolve disputes. This quantitative study uses the descriptive-evaluative method since this study assessed the perspectives to trial by publicity among barangay citizens, officials, and media practitioners. This study surveyed 270 respondents composed of barangay constituents and officials from the three identified barangays of Naga and media practitioners. Results showed that the barangay citizens, officials, and media practitioners are highly aware of trial by publicity regarding objectives, procedure, and judgment. It was also concluded that the trial by publicity is irrefutably one way of influencing the public through media by catching the audience’s attention, giving them what they want to be sure of without in-depth analysis and exploration.